Development of recombinase polymerase amplification assay for the detection of mycobacterium tuberculosis - Salleh, Nur Eyuni Mohd (2022)
The World Health Organization (WHO) has incorporated various strategies to strengthen tuberculosis (TB) control programmes. The current diagnostic tools for TB detection require different levels of laboratory sophistication due to technical complexities, expertise and biosafety requirements in nucleic acid (NA) based TB testing. Therefore, it is challenging to use NA-based assays in resource-constrained settings. With such limitations, there is a need to develop new approaches that can facilitate point-of-care (POC) diagnostics. Recombinase amplification assay (RPA) is an NA-based amplification platform that requires an optimal heat source for accurate diagnosis of a particular disease in a short time. The method is capable of amplifying specific NA at a single, low and constant temperature with minimal amount of sample preparation. In this study, a rapid assay for the detection of Mycobacterium tuberculosis (Mtb) based on the RPA targeting the B9 sequence was developed. The RPA-based detection of Mtb DNA was achieved within 20 minutes at 39°C. The analytical sensitivity of the test was one pg when tested using purified Mtb genomic DNA. The clinical performance of the RPA was evaluated using 387 sputum samples with the culture method as the gold standard. RPA and microscopy were compared to the gold standard in terms of sensitivity, specificity, positive predictive value, negative predictive value, false positive value and false negative value. The results showed that the sensitivity, specificity, positive predictive value, negative predictive value, false positive value and false negative value of RPA were 97.2% (95% CI: 93.5, 99.0), 92.2% (95% CI: 87.6, 95.2), 91.7% (95% CI: 87.8, 95.6), 97.4% (95% CI: 95.2, 99.7), 7.8% (4.2, 11.4), 2.8% (95% CI:0.4, 5.1), respectively, while microscopy had a sensitivity, specificity, positive predictive value, negative predictive value, false positive value and false negative value of 90.6% (95% CI: 85.4, 94.1), 88.8% (95% CI: 83.7, 92.5), 87.7% (95% CI: 83.0, 92.4), 91.5% (95% CI:87.6, 95.4), 11.2% (95% CI:6.9, 15.4) and 9.4% (95% CI:5.2, 13.6), respectively. RPA was found to be more sensitive and specific compared to microscopy, suggesting that the method has the potential to be used as a point-of-care (POC) TB diagnostic tool.